The birds of the republic of colombia: (segunda entrega: accipitridae - picidae) (1949)
Figures given in parentheses are wing measurements from Swann's Monogr. Bds. Prey. Those which do not appear in parentheses are from other published sources, or in most cases they are extreme measurements taken from Colombian specimens by Professor Dugand.